Isolation and Characterization of Cellulose Whiskers from Lampung Sugarcane Bagasse, Indonesia - Afifi, Muhammad Ridho; Aini, Zahratul; Irawadi, Tun Tedja; Purwaningsih, Henny (Department of Mathematics and Science Education, Faculty of Teacher Training and Education, University of Mataram. Jurnal Pijar MIPA colaborates with Perkumpulan Pendidik IPA Indonesia Wilayah Nusa Tenggara Barat, 2025)
Sugarcane bagasse, the fibrous residue from sugar production, is an abundant agricultural waste in Indonesia, especially in Lampung, one of the country’s leading sugarcane-producing provinces. Its high lignocellulosic content makes it a promising alternative source of cellulose. However, effective extraction and conversion into high-value products such as cellulose whiskers require optimized chemical processes. This study aims to isolate cellulose from sugarcane bagasse using alkali and peroxide treatments and convert it into cellulose whiskers through hydrolysis using sulfuric acid (H₂SO₄) at varying concentrations (4–12 M). The objective is to evaluate the optimal acid concentration that produces cellulose whiskers with desirable morphology and crystallinity. Cellulose isolation was achieved through sequential NaOH and H₂O₂ treatments, significantly reducing lignin and hemicellulose content and yielding α-cellulose at 88.37%. Hydrolysis of the purified cellulose was then performed with H₂SO₄. The resulting materials were characterized using FTIR, SEM, XRD, and TGA. FTIR confirmed the removal of non-cellulosic components, while SEM showed that only 10 M H₂SO₄ produced well-defined whiskers with nanoscale dimensions (200–700 nm in length and 10–50 nm in diameter). Lower acid concentrations resulted in incomplete hydrolysis, while excessive degradation occurred at 12 M. XRD analysis revealed an increase in crystallinity to 86.7%, indicating the removal of amorphous regions and successful formation of crystalline whiskers. TGA analysis showed different thermal degradation patterns between isolated cellulose and whiskers, supporting structural transformation. Cellulose whiskers can subsequently be utilized as a reinforcing material in the fabrication of plastic films for water–oil separation and dye adsorption applications in laboratory experiments.